A Study on the Ozone Control Strategy using the OZIPR in the Seoul Metropolitan Area - Lan Jin; Sun-Hwa Lee; Hye-Jung Shin; Yong Pyo Kim (Asian Journal of Atmospheric Environment, 2012)
To establish area specific control strategy for ambient ozone in the Seoul Metropolitan Area (SMA), the maximum ozone concentration in each local government district in the SMA were estimated by using the OZone Isopleth Plotting Package for Research (OZIPR) model. The modeling period was June 2000 and the emission inventory data used were from National Institute of Environmental Research (NIER). Except the islands of Incheon, whole Seoul and Incheon areas were volatile organic compounds (VOCs) limited, i.e., decreasing the oxides of nitrogen (NOX) emission alone may increase the maximum ozone concentration upto certain point. In Gyeonggi, 12 areas were VOCs limited while 12 areas were in between VOCs limited and NOX limited, i.e., decreasing both NOX and VOCs emission may decrease the maximum ozone concentration. Majority of the estimated ozone values were lower than the measured values. The reason could be inaccuracy in emission inventories and/or transport from other areas. The same calculation was carried out for June 2004 and it was found that Seoul was still in the VOCs limited condition.